Motivating Learners to Practice Speaking English - indah, Fristi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
Learning English needs skill and concerns, as speaking is one of the most challenging skills. Many students struggle with self-confidence, anxiety, and lack of opportunities to practice speaking effectively. Motivation plays an important role in encouraging students to overcome these challenges and actively participate in speaking activities. This article focuses on exploring the concept of motivation in English speaking practice and effective methods to develop it in teaching. With reference to some of the theoretical viewpoints, motivation is discussed as a psychological and emotional element that encourages students to achieve certain goals, including communication skills. The article also describes the effect of intrinsic and extrinsic motivation on students' desire to speak and identifies the main methods that teachers can apply to motivate students. These methods include creating a supportive learning environment, interesting and relevant speaking assignments, applying positive reinforcement, and giving positive constructive feedback. By using these methods, teachers can encourage students to develop more confidence, initiative and communication skills when using English especially in speaking skill.